Hydrogel glucomannan-xanthan gum wound dressing with Caesalpinia sappan extract as antibacterial compound - Nadra Khairiah; Nazarni Rahmi; Rais Salim (Kementerian Perindustrian, 2022)
The development of a wound dressing is necessary to accelerate wound closure, promote tissue growth, and reduce scar formation. Hydrogel can be used as an ideal wound dressing. There are many materials that can be used as ingredients in the manufacture of hydrogels such as glucomannan and xanthan gum. The addition of antibacterial compound to wound dressing hydrogels such as sappan wood extract can be used to further improve the wound healing process, and avoid skin infections. In this study, hydrogel glucomannan-xanthan gum was prepared using a concentration of 1% xanthan gum: glucomannan (50:50 and 60:40), 2% xanthan gum: glucomannan (50:50 and 60:40) with the addition of 2% sappan wood extract. Furthermore, the water content, FTIR and antibacterial activity were determinate. The data showed that the hydrogel had excellent physicochemical and antibacterial properties. All the formulation of xanthan gum and glucomannan can formed hydrogels at 37° C and lower. The FTIR result showed the formation of new hydrogen bonds between glucomannan and xanthan gum. The hydrogel added with secang extract was able to inhibit E. coli and S. aureus with an inhibition zone of 7.0 -7.5 mm and 16.25-18.50 mm, respectively. Hydrogel was suitable for application as a wound dressing.